Exploring structural and strategic correlates of difficulties in the internationalisation process of Italian wine SMEs - Christopher Karl Köhr; Luca Camanzi; Giulio Malorgio (Wine Economics and Policy)
Internationalisation has been a key strategy for businesses around the world over the last decades. Nowadays, the European wine sector finds itself in an increasingly competitive international environment, which is characterised by mature and declining per capita wine consumption in traditional markets and increasing competition form new emerging wine producing countries. Structurally, this sector is characterised by a vast majority of family businesses and faces several particularities. This research investigates the perception of difficulties in the internationalisation process of small and medium wineries in two emerging Italian wine exporting regions. It is found that the difficulties perceived in the internationalisation process depend on strategic and structural factors. The strategic factors highlighted in this paper are the degree of international diversification and the geographic scope of a firm's export activities. The structural factors relate to the characteristics of the exported goods, the management and the size of a firm. The findings are discussed in the light of recent developments of Italian wine exports and their implications for the Italian wine sector are derived. Keywords: Internationalisation, SME, Italy